PENINGKATAN KEMAMPUAN MENGHITUNG PERKALIAN MENGGUNAKAN TEKNIK JARI TANGAN PADA PELAJARAN MATEMATIKA SISWA SEKOLAH DASAR - Yarniasti Maiyulita (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Based on the result of the daily tes in mathemathics lesson about multiplication that is in orderly arrangement indicated that the lesson is not success. Whereas, according to the teacher in daily lesson was explained orally and was given some examples, in fact it was given a lot of question for the student exercise, and also give a chance for the students to ask a question, however they not exploit that chance. The low of mastery of multiplication count ability on mathemathics lesson caused it is not right in model of learning and media that was used. So that, the students became not active in study of mathemathics, feel bored, and not listen what explained the teacher. Therefore, to improve multiplication count ability was needed the model of lerning with the right media. One of the model of learning is using the fingers of a hand. This research intends to increase multiplication count ability of the SDN 02 students Muara Panas, class four. The location of this research is in SDN 02 Muara Panas, Bukit Sundi subdistrict. There are 34 student in the class. The data of this research can be got from interview, question naire, obseevation action and evaluation. This research is implemented in two the stage:1) Arrange the lesson plan, 2) Action, 3)Observation, and 4)Analysis. The result of research indicated that adapt to the result of research observation in pre-action is the students that are not active, feel bored, and do not listen what explained the teacher very low in learning.